Amyloid-Beta Induced Changes in Vesicular Transport of BDNF in Hippocampal Neurons. (10th January 2016) - Seifert, Bianca; Eckenstaler, Robert; Rönicke, Raik; Leschik, Julia; Lutz, Beat; Reymann, Klaus; Lessmann, Volkmar; Brigadski, Tanja
Abstract : The neurotrophin brain derived neurotrophic factor (BDNF) is an important growth factor in the CNS. Deficits in transport of this secretory protein could underlie neurodegenerative diseases. Investigation of disease-related changes in BDNF transport might provide insights into the cellular mechanism underlying, for example, Alzheimer's disease (AD). To analyze the role of BDNF transport in AD, live cell imaging of fluorescently labeled BDNF was performed in hippocampal neurons of different AD model systems. BDNF and APP colocalized with low incidence in vesicular structures. Anterograde as well as retrograde transport of BDNF vesicles was reduced and these effects were mediated by factors released from hippocampal neurons into the extracellular medium. Transport of BDNF was altered at a very early time point after onset of human APP expression or after acute amyloid-beta(1-42) treatment, while the activity-dependent release of BDNF remained unaffected. Taken together, extracellular cleavage products of APP induced rapid changes in anterograde and retrograde transport of BDNF-containing vesicles while release of BDNF was unaffected by transgenic expression of mutated APP. These early transport deficits might lead to permanently impaired brain functions in the adult brain.